REALISM AND NATURALISM INTERTWINED: HARDY’S TESS AND DREISER’S CARRIE - Murodjon qizi, Hamzayeva Zebo (Journal of Higher Education and Academic Advancement, 2025)
Objective: In this article written about the intersection of realism and naturalism in Thomas Hardy’s Tess of the d’Urbervilles and Theodore Dreiser’s Sister Carrie. Both novels, though rooted in distinct literary traditions, reveal overlapping aesthetic and thematic concerns, particularly in their treatment of women’s struggles within oppressive social structures. Method: The study draws upon literary criticism, historical context, and narrative analysis to demonstrate how Hardy and Dreiser utilize their respective narrative strategies to reflect the deterministic forces of society while simultaneously allowing for moments of personal agency. Result: Hardy’s lyrical realism intertwines with the fatalistic tone of naturalism, whereas Dreiser’s journalistic detachment reflects a raw, unembellished portrayal of urban life. Novelty: Through comparative analysis, the article highlights how both authors capture the socio-economic pressures, gender roles, and moral constraints of their eras.